Adherence to Statin Therapy and Attainment of LDL Cholesterol Targets in an Outpatient Population of Type 2 Diabetes Patients: Analysis in the DIAbetes and LifEstyle Cohort Twente (DIALECT) - Beernink, Jelle M.; Oosterwijk, Milou M.; van Boven, Job F. M.; Heerspink, Hiddo J. L.; Bakker, Stephan J. L.; Navis, Gerjan; Nijboer, Roos M.; Gant, Christina M.; Haverkate, Heleen; Kruik-Kollöffel, Willemien J.; Laverman, Gozewijn D. (Frontiers in Pharmacology, 2022)
Objective: To assess adherence to statin therapy and its association with sociodemographic data, medical characteristics, LDLc levels and LDLc target attainment in real-world T2D patients treated in secondary care. Research Design and Methods: Cross-sectional analyses were performed on baseline data of 393 patients in the DIAbetes and LifEstyle Cohort Twente (DIALECT). The medication possession ratio (MPR), calculated with pharmacy dispensing data, was used to determine adherence to statins for an intended period of 24 months. Statins were included in the analyses if they were used for at least six consecutive months with at least three dispenses. Adherence was defined as an MPR ≥80%. Associations with adherence were assessed using descriptive statistics and binary logistic regression. Results: Overall, 80% of the patients had a statin prescription and of those, 89% were adherent. The proportion of patients who reached LDLc targets of ≤2.5 mmol/L and <1.8 mmol/L differed significantly between the adherent, nonadherent and non-statin group (90% vs. 74% vs. 46%; P <0.01 and 56% vs. 26% vs. 6%; P <0.01, respectively). Serum LDLc levels were lower in the adherent versus the nonadherent and non-statin group (1.76 ± 0.60 vs. 2.23 ± 0.90 vs. 2.71 ± 0.67 mmol/L; P <0.01). Higher HbA1c levels were independently associated with nonadherence (OR: 1.05, 95% CI 1.01-1.08; P <0.01). Mediation adherence (OR: 2.88, 95% CI 1.04-7.97; P= 0.041) and lower BMI (OR: 0.88, 95% CI 0.81-0.96; P <0.01) were independently associated with attaining the LDLc target of ≤2.5 mmol/L. Conclusions: In patients with T2D treated in secondary care, statin adherence was relatively high and was associated with significantly lower LDLc levels. It is important to identify nonadherence as it appeared an important determinant of failure to reach LDLc targets. The finding that many patients who failed to attain LDLc targets did not receive statin treatment offers an opportunity to improve diabetes care.